2013
DOI: 10.1063/1.4818136
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism and ferroelectricity in epitaxial BiMnO3 ultra-thin films

Abstract: We studied the ferroelectric and ferromagnetic properties of compressive strained and unstrained BiMnO3 thin films grown by rf-magnetron sputtering. BiMnO3 samples exhibit a two-dimensional cube-on-cube growth mode and a pseudo-cubic structure up to a thickness of 15 nm and of 25 nm when deposited on (001) SrTiO3 and (110) DyScO3, respectively. Above these thicknesses, we observe a switching to a three-dimensional island growth mode and a simultaneous structural change to a (00l) oriented monoclinic unit cell.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 26 publications
2
45
0
Order By: Relevance
“…In spite of theoretical predictions that did not find any tendency for ferroelectricity under epitaxial strain [73], ferroelectricity has been demonstrated in strained thin films with polarization values of 16-23 µC.cm −2 [74,75,76], and in La 0.1 Bi 0.9 MnO 3 films [77]. Another claim was made in [78], but the hysteresis loops presented are dominated by dielectric losses and do not prove the ferroelectric character.…”
Section: Coexistence Of Ferroelectricity and Jahn-teller Distortion: mentioning
confidence: 84%
“…In spite of theoretical predictions that did not find any tendency for ferroelectricity under epitaxial strain [73], ferroelectricity has been demonstrated in strained thin films with polarization values of 16-23 µC.cm −2 [74,75,76], and in La 0.1 Bi 0.9 MnO 3 films [77]. Another claim was made in [78], but the hysteresis loops presented are dominated by dielectric losses and do not prove the ferroelectric character.…”
Section: Coexistence Of Ferroelectricity and Jahn-teller Distortion: mentioning
confidence: 84%
“…The scans show that all superlattices grew epitaxially on SrTiO 3 (STO), showing pseudocubic (001) pc refl ections. [ 31 ] No superlattice peaks from the multilayer were observed; however, this does not indicate the lack of a high quality SL-BFO/BMO structure since any minor interface roughening reduces the intensity of these peaks dramatically due to the small difference between scattering factors of BMO and BFO. A minor contribution of monoclinic BMO (<1%) was observed in all fi lms.…”
Section: Doi: 101002/admi201500597mentioning
confidence: 87%
“…It was found that the BMO did not grow layer-by-layer which could be expected since the growth is complicated by the highly volatile Bi as well as the large lattice mismatch between pseudocubic BMO and STO. [ 31 ] It is noted that the interface roughening of our superlattices increased with fi lm thickness as confi rmed by XRR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations